2005
DOI: 10.1021/jo050722e
|View full text |Cite
|
Sign up to set email alerts
|

A New Supported Reagent for the Parallel Synthesis of Primary and SecondaryO-Alkyl Hydroxylamines through a Base-Catalyzed Mitsunobu Reaction

Abstract: The growing field of applications of O-alkyl hydroxylamines in medicinal chemistry and chemical biology has motivated the search for a parallel synthesis. A solid-phase approach based on the alkylation by alcohols of a new supported N-hydroxyphthalimide reagent using a Mitsunobu reaction followed by methylaminolysis has been optimized. This study points out the importance of the linker and a specific base effect for the Mitsunobu reaction. A large variety of alcohols can be used to give with moderate to high y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 86 publications
(137 reference statements)
0
16
0
Order By: Relevance
“…11 (B) The silyl-hydroxylation of olefins bearing electron-withdrawing groups is accomplished by the reaction of NHPI with a silane. The trialkylsilyl radical adds to the olefin to form an intermediate that, when trapped by molecular oxygen, forms the corresponding alcohol.…”
Section: Scheme 1 Abstractsmentioning
confidence: 99%
“…11 (B) The silyl-hydroxylation of olefins bearing electron-withdrawing groups is accomplished by the reaction of NHPI with a silane. The trialkylsilyl radical adds to the olefin to form an intermediate that, when trapped by molecular oxygen, forms the corresponding alcohol.…”
Section: Scheme 1 Abstractsmentioning
confidence: 99%
“…376 are prepared in high purity [549] under Mitsunobu conditions by solid-phase synthesis of the polymer-supported N-hydroxyphthalimide 374 with alcohols, triphenylphosphine-cyclic sulfamide betaine, [550] and diethyl azodicarboxylate in dry tetrahydrofuran 40.5.2 Acyclic O-Alkyl-, O,N-Dialkyl-, and Trialkylhydroxylamines to give 375, followed by methylaminolysis (Scheme 145). The triphenylphosphine-cyclic sulfamide betaine efficiently promotes coupling between alcohols and the N-OH group; the presence of imidazole increases the yield of the hydroxylamines 376.…”
Section: Diverse O-(arylalkyl)and O-(hetarylalkyl)hydroxylamines and mentioning
confidence: 99%
“…The triphenylphosphine-cyclic sulfamide betaine efficiently promotes coupling between alcohols and the N-OH group; the presence of imidazole increases the yield of the hydroxylamines 376. [549] N Boc 92 [549] NHBoc Pr i 83 [549] NHBoc Pr i 82 [549] NHBoc 72 [549] Pr i NHBoc 86 [549] Pr i NHBoc 82 [549] S 90 [549] R 1 [549] N O N quant [549] N S N quant [549] N S N quant [549] Solid-phase syntheses of resin-bound O-alkylhydroxylamines 377-379 and further transformation to hydroxamic acids, designed as matrix metalloproteinase inhibitors, are successfully performed by treatment of Wang resin with N-hydroxyphthalimide, triphenylphosphine, and diethyl azodicarboxylate, followed by hydrazinolysis (Scheme 146). [551] Scheme A facile and economic synthesis of (tert-alkoxy)amines 381 involves reaction of tertiary alcohols with stoichiometric boron trifluoride-diethyl ether complex and N-hydroxyphthalimide to give the corresponding N-(tert-alkoxy)phthalimides 380 in fair to good yields, which by subsequent (methyl)hydrazinolysis afford alkoxyamines 381 (Scheme 147).…”
Section: Diverse O-(arylalkyl)and O-(hetarylalkyl)hydroxylamines and mentioning
confidence: 99%
“…[49] More recently, it has been demonstrated that its incorporation into peptides can induce and stabilize turns or helical structures. [50] In this context, a solid-phase approach based on the alkylation by alcohols of a new supported N -hydroxyphthalimide reagent 100 using a Mitsunobu reaction followed by methylaminolysis has been recently reported; [51] it was used to synthesize in parallel a large diversity of O-alkyl hydroxylamines 103 (Scheme 3.27).…”
Section: Typical Experimental Proceduresmentioning
confidence: 99%
“…To a solution of 2-hydroxy-1,3-dioxoisoindoline-5-carboxylic acid ( General procedure for cleavage (Scheme 3.27) [51] The resin was suspended in trichloromethane/methanol ( …”
Section: Typical Experimental Procedures Preparation Of N-hydroxyphthmentioning
confidence: 99%